2019
DOI: 10.3390/soilsystems3020026
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Feedstock Wood Chemistry Strongly Influences Biochar Liming Potential

Abstract: Chars intended for use as soil amendment (“biochars”) vary greatly in their chemical and physical properties. In the present study, 19 Canadian temperate wood feedstocks were charred across a range of pyrolysis temperatures from 300–700 °C. The resulting 95 biochars were tested for their physio-chemical properties and liming capacity. Data indicated increasing base cation concentrations including Ca, Mg, and K (elements that characteristically form liming compounds, i.e., carbonates) as pyrolysis temperature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 66 publications
4
37
0
2
Order By: Relevance
“…Pinewood biochars (WB) were much more limey than bamboo biochars (BB), but their EC was less than half as large, in accordance with lower ash contents. Biochars generally have a substantial liming capacity, to an extent due to mineral content present in the feedstock [4]. Significant differences (p < 0.05) in pH were found between replicates showing higher values of pH in biochars with a higher degree of thermal alteration, in agreement with previous works (e.g., [15,21]).…”
Section: Chemical Properties Of the Biocharssupporting
confidence: 89%
See 3 more Smart Citations
“…Pinewood biochars (WB) were much more limey than bamboo biochars (BB), but their EC was less than half as large, in accordance with lower ash contents. Biochars generally have a substantial liming capacity, to an extent due to mineral content present in the feedstock [4]. Significant differences (p < 0.05) in pH were found between replicates showing higher values of pH in biochars with a higher degree of thermal alteration, in agreement with previous works (e.g., [15,21]).…”
Section: Chemical Properties Of the Biocharssupporting
confidence: 89%
“…According to Keiluweit et al [53] decomposition of cellulose occurs rapidly at low temperatures (between 230 and 400 • C), while lignins decompose in a wider range of temperatures (160-900 • C). The differences in the patterns of stove temperatures between bamboo and wood, observed in Figure 1, may obey to differences in the biomass composition [4], due to the temperatures at which decomposition reactions take place, such as oxidation and dehydration. As previously discussed, higher contents of metallic cations have been related to lower pyrolysis temperatures [36][37][38].…”
Section: Chemical Properties Of the Biocharsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, increased concentration of K in biochar, together with Mg and Ca, functions as a liming agent to neutralise acid soils [109]. Meta-analysis of the literature showed that biochar application led to a reduction in the acidity of the soil in multiple studies [110].…”
Section: Biochar As a Liming Inputmentioning
confidence: 99%